Comparative Planetology of Magnetic Effects in Ultrahot Jupiters: Trends in High-resolution Spectroscopy - Hayley Beltz; Emily Rauscher (The Astrophysical Journal)
Ultrahot Jupiters (UHJs), being the hottest class of exoplanets known, provide a unique laboratory for testing atmospheric interactions with internal planetary magnetic fields at a large range of temperatures. Thermal ionization of atmospheric species on the dayside of these planets results in charged particles becoming embedded in the planet’s mostly neutral wind. The charges will resist flow across magnetic field lines as they are dragged around the planet and ultimately alter the circulation pattern of the atmosphere. We model this process to study this effect on high-resolution emission and transmission spectra in order to identify observational signatures of the magnetic circulation regime that exist across multiple UHJs. Using a state-of-the-art kinematic MHD/active drag approach in a 3D atmospheric model, we simulate three different UHJs with and without magnetic effects. We postprocess these models to generate high-resolution emission and transmission spectra and explore trends in the net Doppler shift as a function of phase. In emission spectra, we find that the net Doppler shift before and after secondary eclipse can be influenced by the presence of magnetic drag and the wavelength choice. Trends in transmission spectra show our active drag models consistently produce a unique shape in their Doppler shift trends that differs from the models without active drag. This work is a critical theoretical step to understanding how magnetic fields shape the atmospheres of UHJs and provides some of the first predictions in high-resolution spectroscopy for observing these effects.